Patrimonio alimentario y gastronómico del cantón Salcedo - Benavides Moya, Yajhaira Guadalupe (2023)
The current research focused on characterizing the existing alternatives white the purpose be identifying the food and gastronomic heritage from Salcedo canton from Cotopaxi province. Which it was made a diagnosis by using a qualitative approach, since this helps to identify important data and thus getting results based on study area cultural aspects. Through a primary and secondary information source bibliographic review into scientific articles, magazines, books and digital magazines, it could be developed the first aim analysis, describing that the canton has 5 rural parishes, which are Antonio Jose Holguin, Cusubamba, Mulalillo, Mulliquindil, Panzaleo and 1 urban parish, being this San Miguel, by taking into account that agriculture, gastronomy and livestock are they main economic income from canton, For de second aim, it was appied and ethnographic method which allowed to make an approach to the people, who are fundamental base in the research, this was done with key foundations for getting data, after it was applied the records from Heritage Culture National institute, delivering as a result 9 Gastronomic developments inventoried in the Salcedo canton with 4 foods considered heritage by the Heritage and Culture Ministry. In the third aim, it made a necessary compilation, for the a gastronomic guide elaboration and design, what allows the tourist to recognize the history, which keep the most ancestral traditional dishes from canton, by emphasizing the cultural identity preservation and rescue that save the food, its ritual, festive and daily uses, as well as its ancestral preparation techniques.